Surface influence on the marine and coastal Antarctic atmosphere - Valkonen, Teresa (Helsingin yliopisto, 2013)
The Antarctic region plays an important role in the global climate system, and it contributes to the future of global climate through changes in regional factors, such as sea ice, atmospheric circulation patterns and moisture distribution. The aim of this thesis is to improve the understanding of the influence of the Earth surface on the marine and coastal Antarctic atmosphere. The thesis outlines the characteristics of typical phenomena of the Antarctic environment both near the surface and higher in the atmosphere, and describes the challenges related to numerical modelling in the region. The work is based on combined use of several observational data sets and regional numerical modelling. Marine atmosphere and its reprensentation in regional modelling was studied based on observational data collected on two research projects called 'Short Timescale Motion of Pancake Ice', and 'Ice Station Polarstern'. The coastal atmosphere was studied based on data from the Movable Atmospheric Radar for Antarctica from Queen Maud Land and the Integrated Global Radiosonde Archive from 11 coastal stations. Model simulations were made using two regional-scale atmospheric models: the Fifth-Generation Pennsylvania State University/National Center for Atmospheric Research Mesoscale Model (MM5) and the Weather Research and Forecasting (WRF) model. The boundary layer over the marine Antarctic was found to be strongly governed by the presence or absence of sea ice. The major challenges related to the modelling of the atmosphere over Antarctic sea ice were associated with clouds, boundary layer processes and sea ice and snow description. The model sensitivity to different physical parameterisation schemes was most profound in the lowest parts of the atmosphere. The results confirm that numerical simulations reproduce relatively accurately the basic meteorological surface variables, such as temperature, humidity, air pressure, wind speed and wind direction, over ice-covered ocean, but the turbulent and radiative fluxes that affect ...